Gastrointestinal motility in elderly patients with well-controlled type 2 diabetes mellitus - Sena, Erika M A B.; Silva, Dianna V L.; Américo, Madileine F.; Nascimento, Jhony W G.; Miranda, José R A. [UNESP]; Corá, Luciana A. (FapUNIFESP (SciELO), 2022)
Background – Gastrointestinal (GI) motility disorders in type 2 diabetes mellitus (T2DM) are common. However, the endpoints in well-controlled T2DM in elderly patients are barely understood. Objective – To evaluate GI transit and gastric myoelectric activity in elderly patients with T2DM who were undergoing treatment with metformin and to compare them with non-diabetic healthy controls. Methods – A total of thirty participants were enrolled in this study: young non-diabetic (n=10), elderly non-diabetic controls (n=10), and patients with T2DM managed with met-formin (n=10). After fasting overnight, the participants ingested a standard meal and magnetic markers for non-invasive monitoring of GI transit and gastric contractility using the alternating current biosusceptometry and electrogastrography techniques. Results – Mean gastric emptying time, mean colon arrival time, and mean intestinal transit time were determined. There were no significant differences between the groups and in the parameters evaluated (P>0.05). The frequency and amplitude of gastric myoelectric activity were not different between groups; however, abnormal rhythmic index and the half-bandwidth were slightly higher for both elderly diabetic and non-diabetic groups compared with the young adults (P<0.01 and P<0.05, respectively). Conclusion – Our study showed unaltered gastric emptying and intestinal transit in T2DM patients with good glycemic control, and suggest changes in the gastric electrical activity can be a part of aging.
Motilidade gastrintestinal em pacientes idosos com diabetes mellitus tipo 2 bem controlado.
Keywords: Elderly; gastrointestinal motility; glycemic control; metformin; type 2 diabetes mellitus